The last lifeboat - Gaynor, Hazel (Berkley, 2023)
"Inspired by a remarkable true story, a young teacher evacuates children to safety across perilous waters, in a moving and triumphant new novel from New York Times bestselling author Hazel Gaynor. 1940, Kent: Alice King is not brave or daring--she's happiest finding adventure through the safe pages of books. But times of war demand courage, and as the threat of German invasion looms, a plane crash near her home awakens a strength in Alice she'd long forgotten. Determined to do her part, she finds a role perfectly suited to her experience as a schoolteacher--to help evacuate Britain's children overseas. 1940, London: Lily Nichols once dreamed of using her mathematical talents for more than tabulating the cost of groceries, but life, and love, charted her a different course. With two lively children and a loving husband, Lily's humble home is her world, until war tears everything asunder. With her husband gone and bombs raining down, Lily is faced with an impossible choice: keep her son and daughter close, knowing she may not be able to protect them, or enroll them in a risky evacuation scheme, where safety awaits so very far away. When a Nazi U-boat torpedoes the S. S. Carlisle carrying a ship of children to Canada, a single lifeboat is left adrift in the storm-tossed Atlantic. Alice and Lily, strangers to each other--one on land, the other at sea--will quickly become one another's very best hope as their lives are fatefully entwined"--